Human resources for primary health care in sub-Saharan Africa: progress or stagnation? - Willcox, Merlin L; Peersman, Wim; Daou, Pierre; Diakité, Chiaka; Bajunirwe, Francis; Mubangizi, Vincent; Mahmoud, Eman Hassan; Moosa, Shabir; Phaladze, Nthabiseng; Nkomazana, Oathokwa; Khogali, Mustafa; Diallo, Drissa; et al. (Human Resources for Health, 2015)
Background: The World Health Organization defines a “critical shortage” of health workers as being fewer than 2.28 health workers per 1000 population and failing to attain 80% coverage for deliveries by skilled birth attendants. We aimed to quantify the number of health workers in five African countries and the proportion of these currently working in primary health care facilities, to compare this to estimates of numbers needed and to assess how the situation has changed in recent years. Methods: This study is a review of published and unpublished “grey” literature on human resources for health in five disparate countries: Mali, Sudan, Uganda, Botswana and South Africa. Results: Health worker density has increased steadily since 2000 in South Africa and Botswana which already meet WHO targets but has not significantly increased since 2004 in Sudan, Mali and Uganda which have a critical shortage of health workers. In all five countries, a minority of doctors, nurses and midwives are working in primary health care, and shortages of qualified staff are greatest in rural areas. In Uganda, shortages are greater in primary health care settings than at higher levels. In Mali, few community health centres have a midwife or a doctor. Even South Africa has a shortage of doctors in primary health care in poorer districts. Although most countries recognize village health workers, traditional healers and traditional birth attendants, there are insufficient data on their numbers. Conclusion: There is an “inverse primary health care law” in the countries studied: staffing is inversely related to poverty and level of need, and health worker density is not increasing in the lowest income countries. Unless there is money to recruit and retain staff in these areas, training programmes will not improve health worker density because the trained staff will simply leave to work elsewhere. Information systems need to be improved in a way that informs policy on the health workforce. It may be possible to use existing resources more cost-effectively by involving skilled staff to supervise and support lower level health care workers who currently provide the front line of primary health care in most of Africa
Keywords: Human resources for health; Primary health care; Review; Sudan; Mali; Uganda; Botswana; South Africa